2018
DOI: 10.1182/blood-2018-154
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Combination of Elotuzumab, Lenalidomide, and Dexamethasone in High-Risk Smoldering Multiple Myeloma

Abstract: Background This study aimed to determine the benefit of early therapeutic intervention with the combination of elotuzumab, Lenalidomide, and Dexamethasone in patients with high-risk smoldering multiple myeloma (SMM). ClinicalTrials.gov Identifier: NCT02279394. Aims The overarching objective of this trial is to determine progression free survival to symptomatic multiple myeloma (MM). Furthermore, the study examined whether genomic studies can help in determining pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Elo-len-dex was tested in a phase 2 randomized study (NCT02279394) dedicated to high-risk SMM, according to the Mayo Clinic criteria or one of the new proposed criteria [ 5 ] (patients with one of the malignancy biomarkers were excluded). Fifty patients were enrolled and received Elo-len with or without the addition of dex [ 22 ]. The primary analysis of the trial, currently on-going, showed that 84% of the patients achieved at least a partial response (PR), in a median time of 2.8 months, with 6% CR and 37% VGPR.…”
Section: Discussionmentioning
confidence: 99%
“…Elo-len-dex was tested in a phase 2 randomized study (NCT02279394) dedicated to high-risk SMM, according to the Mayo Clinic criteria or one of the new proposed criteria [ 5 ] (patients with one of the malignancy biomarkers were excluded). Fifty patients were enrolled and received Elo-len with or without the addition of dex [ 22 ]. The primary analysis of the trial, currently on-going, showed that 84% of the patients achieved at least a partial response (PR), in a median time of 2.8 months, with 6% CR and 37% VGPR.…”
Section: Discussionmentioning
confidence: 99%
“…Elotuzumab has also been evaluated in combination with lenalidomide and dexamethasone (EloRd) in patients with high-risk SMM in another phase 2 trial (NCT02279394) [ 60 ]. EloRD induced PR or better in 41 out of 50 patients, including three CR and 18 VGPR.…”
Section: Monoclonal Antibody-based Treatments For Smoldering Myelomentioning
confidence: 99%
“…Neutropenia (6%), thrombocytopenia (11%), infection (18%), and rash (9%) were among the grade 3-4 adverse events reported. Another trial evaluating treatment for active MM in SMM involved a combination of monoclonal antibody directed at SLAMF7, elotuzumab (Elo) with Rd [49]. In total, 50 eligible high-risk SMM patients received Elo-Rd induction for up to 8 cycles, followed by maintenance with Elo (monthly) and lenalidomide maintenance up to a total of 24 cycles.…”
Section: Treatment and Other Ongoing Studiesmentioning
confidence: 99%